TINJAUAN YURIDIS PERTANGGUNGJAWABAN PIDANA KEJAHATAN CYBER ILLEGAL CONTENTS DALAM JASA PAID PROMOTE DI MEDIA SOSIAL - Halilintar Halilintar; Mexsasai Indra; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
E-Commerce activities are not an unusual thing in people's lives, but have become routine along with the development of information technology. The presence of social media makes it very easy for the public in all activities, both information exchange and business transactions. Business transactions that have become an existence for writers, namely Paid Promote and Endorse, are promoted by public figures in social media applications, namely Instagram.However, in online transactions there are still many victims of fraud as a result of E-Commerce which is promoted by promoted and endorsed actors. So far the authors have reviewed according to Article 45A paragraph 1 of Law Number 19 of 2016 on amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, which have not clearly and clearly regulated the types of crimes of Cyber Illegal Content with the modus operandi of services paid to promote in the media social. As a result, the perpetrators cannot be held responsible for the crime.This type of research is normative legal research, namely using library research in data search and examining the subject matter according to the scope and identification of problems through a statutory approach carried out by examining statutory regulations and regulations related to the legal issues under study.The result of this research is that the promoted and endorsed offenders can be convicted if they fulfill the elements of a criminal act with a fraud mode that is misleading consumers as regulated in Article 45A paragraph 1 of the ITE Law and if they are proven to be deceiving and misleading others, they can be held responsible for the crime who feel aggrieved and troubled by the crime of participation as regulated in Article 55 of the Criminal Code concerning Inclusion of Crimes.Keywords: Criminal Accountability Crime- Cyber Illegal Contents in Paid Promote on Social Media.